Design and installation peculiarities of monolithic concrete floor - Žiogas, Vigantas; Juočiūnas, Svajūnas (Journal of Civil Engineering and Management, 2005)
Monolithic concrete floors are frequently designed as plain concrete slabs. The purpose of the plain concrete floor is to transmit loading from its source to the subgrade with minimal distress. The magnitude of these stresses depends on factors such as the subgrade strength, solution of construction, the quality of construction, the magnitude and character of loads. Here is presented the joint spacing for various construction solutions of concrete floor. In practice, joint spacing should be corrected by evaluating rheological properties of concrete mix, type of aggregate, its volumetric concentration and impurity. The direct expenditures of main construction layers were investigated and used for optimization the technologies installation of monolithic concrete floors. The initial data for evaluating the multiple criteria were calculated by estimating the real and practical characteristics, which are represented in this paper. Multiple criteria complex proportional evaluation is used to find a rational decision installation of monolithic concrete floors.Monolitinių betoninių grindų projektavimas ir įrengimo technologijų ypatumaiSantraukaAnalizuojamos monolitinių betoninių grindų projektavimo, įrengimo technologijų ir vykdytojų parinkimo problemos bei šių veiksnių įtaka grindų kokybei ir efektyvumui. Nagrinėjama metalinio pluošto kiekio, jo techninių charakteristikų įtaka betono stipriui lenkiant, įvertinant betono stiprio klasę ir monolitinių betoninių grindų nuovargį. Įvairiems monolitinių betoninių grindų konstrukciniams sprendimams pateikiami siūlių išdėstymo sprendimai, atsižvelgiant į grindų storį, armavimo tipą ir naudoto betono mišinio charakteristikas. Efektyviai grindų įrengimo technologijai nustatyti atlikta monolitinių betoninių grindų pagrindinių konstrukcinių elementų įrengimo išlaidu lyginamoji analize. Remiantis konstrukciniu sprendimu, technologiju ekonominio ivertinimo realiais duomenimis ir pritaikius kompleksinio proporcingumo metodą, atliktas monolitinių betoninių grindų įrengimo technologijų daugiakriterinis įvertinimas.Raktiniai žodžiai: monolitinės betoninės grindys, projektavimas, grindų storis, siūlių išdėstymas, armavimas, įrengimas, tiesioginės išlaidos, daugiakriterinis įvertinimas.First Published Online: 14 Oct 2010